The Relationship Between The Role of Cadres and The Behavior of Mothers in Stunting Prevention at Posyandu Toddler Mancar Village Jombang Regency - Ana, Karisma Dwi; Fiddaroini, Fakhrun Nisa’; Rozi, Fahrur (Adi Husada Nursing Journal, 2024)
Stunting is short or very short of its age caused by inadequate chronic nutritional intake. The low role of cadres is one of the causes that affects maternal behavior in the prevention that will be carried out. This study aimed to determine the relationship between the role of cadres and maternal behavior in stunting prevention in the posyandu toddler. This research design used a cross sectional approach. The population was toddlers Posyandu in Mancar village, jombang regency with a sample size of 68 respondents and using a total sampling technique. Data collection tools in the form of questionnaires on the role of cadres and maternal behavior in stunting prevention, as well as tests data analysis using the spearman rank test significant rate 0.05. The results of the study showed that 51 respondents (75.0%) and mothers under five had less behavior in stunting prevention as many as 59 respondents (86.8%). The results of the Spearman Rank statistical test obtained a significant value of ρ < α (α = 0.05), which is 0.000 < 0.05, meaning that H1 is accepted, so there is a relationship between the role of cadres and maternal behavior in stunting prevention at the Toddler Posyandu in Mancar Village, Jombang Regency. The role of a good cadre can create the behavior of mothers under five in good prevention. The role of health workers or posyandu cadres is very important in realizing good stunting prevention knowledge and behavior so that stunting events can be reduced.